Steward and cook of whaling schooner Era, Hudson Bay, Canadian Arctic - Comer, George (Creator) (Ownership Statement: Mystic Seaport, 1897)
Two men stand in front of covered whaleboat, Hudson Bay, Canadian Arctic, ca. 1897-1899. The men are identified as the ""steward and cook, schooner ERA, 1897-99."" Infrastructure Livelihood Title supplied by cataloger. Information from original envelope identifies this as Photo 199, A 57. In his journal for the 1897 voyage of the Era, Captain George Comer identifies the steward, whose name was George Reddick, as being a black man from the American south. He states that the cook, Alexander Samuel, is from the island of St. Helena. He also indicates that the steward was one of the men rescued by Comer and his crew the previous year, from the wrecked whaling vessel Desdemona. The schooner Era was built in 1847 at Boston, Massachusetts. She was a New London whaling vessel until her last voyage out of that port in 1892; her masters included James Monroe Buddington and John O. Spicer. Captain George Comer of East Haddam served on her as mate under Captain Spicer. Comer was later master of the Era for several Arctic voyages out of New Bedford, 1895-1906. She was wrecked off Miquelon Island, July 27, 1906. Citation: Captain George Comer and the Arctic / by Fred Calabret